A self-compacting concrete and a process for its preparation
Patent Information
- Application Number
- CN202611039687.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-14
AI Technical Summary
然而,现有技术仍存在明显局限:其一,多数胶囊为单层结构,其触发机制单一,在复杂的混凝土内部环境中响应可靠性不足,易发生误触发或该触发时不触发;其二,修复剂的释放往往依赖简单的扩散或一次性破裂,释放效率低、剂量不可控,难以充分填充裂纹,尤其是对动态扩展的微裂纹修复效果有限;其三,胶囊的机械强度与施工耐受性之间存在矛盾,强度过低易在拌合阶段提前破损,过高则可能在需要时无法有效触发,导致修复功能失效
1、由于本申请通过引入智能双响应骨料,并结合特定的制备工艺,赋予混凝土卓越的主动自修复能力和长效耐久性。当混凝土产生微裂纹时,骨料外壳首先在应力刺激下精准破裂,内部遇水膨胀层随即产生强大驱动力,促使载体缓释内核中的自愈合剂充分释放至裂缝,并通过化学反应生成致密、稳固的愈合产物,从而自动、高效地修复损伤,恢复结构的完整性与力学性能,显著提升抗渗性、耐腐蚀性及疲劳寿命。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, and in particular to a self-compacting concrete and its preparation process. Background Technology
[0002] Self-compacting concrete, due to its excellent workability, can fill complex formwork and dense reinforcement under its own weight, significantly improving construction efficiency and project quality, and has been widely used in modern civil engineering. However, like all cement-based materials, concrete inevitably develops microcracks during hardening and long-term service due to factors such as load, shrinkage, temperature changes, and environmental erosion. These microcracks are not only the starting point for the degradation of structural mechanical properties, but also provide a rapid pathway for the intrusion of harmful media such as moisture, chloride ions, and sulfates. They are key factors leading to steel corrosion, freeze-thaw damage, performance deterioration, and ultimately seriously threatening the durability and service life of the structure.
[0003] To address this challenge, endowing concrete with self-healing capabilities has become an important research direction in the field of materials science in recent years. Existing self-healing technologies mainly include microbial repair, capsule repair, and vascular network repair. Among them, capsule repair technology, which involves pre-embedding microcapsules containing repair agents in concrete, releases the repair agent upon crack formation to achieve repair, is a relatively practical approach. However, existing technologies still have significant limitations: First, most capsules are single-layer structures with a single triggering mechanism, resulting in insufficient reliability in the complex internal environment of concrete, prone to false triggering or failure to trigger when required; second, the release of the repair agent often relies on simple diffusion or one-time rupture, leading to low release efficiency, uncontrollable dosage, and difficulty in fully filling cracks, especially with limited repair effects on dynamically expanding microcracks; third, there is a contradiction between the mechanical strength and construction tolerance of the capsules, as excessively low strength may cause premature breakage during the mixing stage, while excessively high strength may prevent effective triggering when needed, leading to failure of the repair function. Summary of the Invention
[0004] To address the aforementioned issues, this application provides a self-compacting concrete and its preparation process.
[0005] Firstly, this application provides a self-compacting concrete, which adopts the following technical solution: A self-compacting concrete comprises the following raw materials in parts by weight: The composition includes 400-500 parts of cementitious material, 700-800 parts of coarse aggregate, 750-850 parts of fine aggregate, 140-160 parts of water, 10-20 parts of intelligent dual-response aggregate, and 2-4 parts of polycarboxylate superplasticizer. The intelligent dual-response aggregate is a functional particle with a core-shell structure, which is encapsulated with a self-healing agent.
[0006] By adopting the above technical solution, a smart dual-response aggregate with a core-shell structure is introduced, which works in synergy with the early expansion component in time and space to improve the volume stability and durability of concrete. When microcracks occur inside the concrete due to load or environmental factors, the core-shell structure of the smart aggregate breaks under dual-response stimuli such as stress or chemical changes, releasing the internally encapsulated self-healing agent. After the healing agent comes into contact with the cementitious material, it triggers a reaction, actively filling and bonding the cracked area, thereby restoring the integrity and mechanical properties of the structure.
[0007] Optionally, the preparation of the intelligent dual-response aggregate includes the following steps: (1) Preparation of core: The self-healing agent and the carrier material are mixed at a weight ratio of 1:(0.6-1.4) to obtain a mixture. 4-6% by mass of the binder solution is added to granulate the mixture to form core particles with a particle size of 0.5-1.5 mm. The mixture is then dried. (2) Coating intermediate layer: The expansive component slurry is coated onto the surface of the core particles using a fluidized bed spraying method, and the intermediate layer is formed after drying; (3) Coating the outer shell: The polymer coating solution is coated on the outer surface of the intermediate layer by fluidized bed spraying. After drying, an outer shell with a thickness of 30-100μm is formed to obtain the smart dual-response aggregate with a particle size of 1-5mm.
[0008] By employing the aforementioned technical solution, a multi-level core-shell system consisting of a core, intermediate layer, and outer shell ingeniously achieves the encapsulation, protection, and controlled release of the internal self-healing agent. When cracks occur inside the concrete, leading to localized stress concentration or changes in the chemical environment, the outer shell of this intelligent aggregate selectively fractures first under the stimulation of a dual mechanical-chemical response. Subsequently, the exposed intermediate layer expands significantly upon contact with water, generating internal compressive force, thereby completely crushing and dispersing the core, prompting the self-healing agent to be released in large quantities and fully flow into the crack space. Its beneficial effects lie in the fact that this multi-stage synergistic triggering and release mechanism greatly enhances the aggregate's sensitivity to micro-damage and response reliability, ensuring that the self-healing agent can be efficiently activated and utilized at the first moment of crack occurrence, overcoming the shortcomings of simple capsules that are prone to failure or insufficient release. Simultaneously, the dense outer shell provides robust protection for the core during concrete mixing and hardening, preventing premature leakage or failure during construction. Ultimately, this enables the concrete to acquire an active repair capability that occurs synchronously with damage and intelligently matches it, significantly enhancing the structure's toughness, durability, and service safety.
[0009] Optionally, the self-healing agent is any one of magnesium calcium silicate or sodium silicate.
[0010] By employing the above-mentioned technical solutions, sodium silicate can rapidly dissolve in the moisture-filled environment of cracks, reacting with calcium ions in the cement matrix to form calcium silicate gel, effectively bonding to the crack surface. Magnesium calcium silicate, on the other hand, can react with infiltrated carbon dioxide and moisture in the humid microenvironment of the cracks, generating carbonates and gel-like products that gradually fill the crack space. Both substances can adapt to the chemical environment within the cracks, generating a stable new healing body through continuous chemical reactions. This not only exhibits excellent chemical compatibility and physical adhesion to the original concrete matrix, effectively restoring the integrity and mechanical properties of the structure, but also significantly improves the density of the repaired area, thereby permanently blocking the intrusion channels of moisture and harmful ions. This active healing, achieved at a chemical level, surpasses physical filling, giving concrete a stronger and more durable self-healing ability, fundamentally enhancing the durability and service life of the structure.
[0011] Optionally, the carrier material is polylactic acid.
[0012] By adopting the above technical solution and selecting polylactic acid (PLA) as the carrier material, a key environmental responsiveness and controllable release mechanism are introduced into the core self-healing functional system. As a polymer that can degrade in alkaline environments, after the outer shell of the smart aggregate cracks, the self-healing agent core encapsulated within it is exposed to the alkaline environment of the concrete pore fluid. The PLA carrier then undergoes controllable hydrolytic degradation. This process not only gradually releases the internally loaded self-healing agent, but its degradation rate is also dynamically correlated with the humidity, alkalinity, and other conditions of the crack environment, thus achieving a match between the release of the self-healing agent and the crack propagation process. This design ensures a continuous, slow-release supply of the repair material, rather than a one-time burst release, greatly extending the active repair window and allowing the concrete to retain its repair potential for subsequent microcracks. Simultaneously, the biocompatibility and ultimate degradation characteristics of PLA itself avoid harmful chemical residues that could damage the long-term performance of the concrete, achieving intelligent repair while also considering the environmental friendliness of the material and the long-term compatibility with the matrix.
[0013] Optionally, the expandable component slurry includes 60-80 parts of calcium sulfoaluminate and 20-40 parts of a 3-5% aqueous solution of hydroxypropyl methylcellulose.
[0014] By employing the above technical solution, when the aggregate shell cracks due to crack propagation, the infiltrated water rapidly activates the calcium sulfoaluminate in the intermediate layer, causing it to undergo a rapid hydration reaction and produce significant volume expansion. This expansion force creates strong internal pressure within the sealed aggregate space. In this process, the hydroxypropyl methylcellulose solution not only acts as a carrier for uniformly dispersing and binding the expansion components, but also regulates the hydration reaction process through its thickening and water-retaining properties, ensuring continuous and controllable growth of the expansion force. This water-triggered, inside-out, controllable expansion behavior provides a powerful and direct mechanical driving force for the final release of the self-healing agent. It effectively and thoroughly breaks down and disperses the core physically, forcing the internal self-healing agent to be fully and rapidly squeezed and transported to all areas of the crack. This overcomes the problems of incomplete release and slow response caused by relying solely on diffusion, further improving the various properties of self-compacting concrete.
[0015] Optionally, the polymer coating solution is obtained by dissolving 5-15 parts of ethyl cellulose in 85-95 parts of an organic solvent.
[0016] By employing the above-mentioned technical solution, ethyl cellulose, after being dissolved in an organic solvent, can form a continuous, dense, and somewhat brittle polymer film on the aggregate surface through a fluidized bed process. This outer shell is insoluble in water and can remain stable during concrete mixing and hardening, effectively sealing and protecting the internal active ingredients. However, when microcracks occur in the concrete, leading to localized stress concentration, this brittle coating will preferentially rupture under stress, thereby exposing the internal expansive intermediate layer. This mechanically triggered mechanism ensures that the aggregate response is highly synchronized with the location and timing of damage, avoiding false triggering caused by slow factors such as chemical erosion. At the same time, the density of the outer shell fundamentally prevents premature erosion of the core by moisture and alkaline environments during construction, ensuring the long-term storage stability of the self-healing capability.
[0017] Optionally, the raw material may also include 2-5 parts of calcium oxide.
[0018] By adopting the above technical solution, calcium oxide rapidly hydrates upon contact with water to generate calcium hydroxide and release heat. This process not only significantly increases the alkalinity inside the concrete, creating the necessary conditions for the alkaline degradation of the polylactic acid carrier in the intelligent aggregate, thus ensuring the effective release of the self-healing agent, but also accelerates the early reaction of the cementitious system and optimizes the pore structure through the exothermic hydration. The generated calcium hydroxide can further react with carbon dioxide in the air or the self-healing agent to generate precipitates such as calcium carbonate, which synergistically fill micropores and cracks with the self-healing products. Its beneficial effects are that this component actively creates a more favorable chemical and physical environment for intelligent repair at the matrix level, enhancing the reliability and efficiency of the repair system; at the same time, its micro-expansion and filling effect enhances the early compaction and long-term carbonation resistance of the concrete, organically combining the material's self-compacting properties, early strength development, and long-term intelligent repair capabilities, ultimately achieving a comprehensive improvement in the durability of the structure from the micro to the macro level.
[0019] Secondly, this application provides a method for preparing self-compacting concrete, which adopts the following technical solution: A method for preparing self-compacting concrete includes the following steps: Mix the cementitious materials, fine aggregates and polycarboxylate superplasticizer evenly, add 70-80% of the total water, stir to form a uniform slurry, add coarse aggregates and the remaining water, stir evenly, finally add intelligent dual-response aggregates and the remaining superplasticizer, stir for 30-60 seconds and then discharge.
[0020] By adopting the above technical solution, a highly fluid slurry is first formed using a portion of water, cementitious materials, and fine aggregates. This lays a uniform matrix for the system and fully wets the particle surface. Subsequently, coarse aggregates are added, allowing them to be fully coated by the slurry, avoiding segregation and ensuring the final self-compacting properties. The most crucial step is to place the intelligent dual-response aggregate in the final stage and mix it in gently. This significantly shortens the time the aggregates are subjected to mechanical shearing and friction during mixing, effectively preventing their brittle outer shell from cracking prematurely due to external forces during construction, thus ensuring the long-term storage stability of the self-healing function.
[0021] In summary, this application has the following beneficial effects: 1. This application, by introducing intelligent dual-response aggregates and combining them with a specific preparation process, endows concrete with superior active self-healing capabilities and long-term durability. When microcracks appear in the concrete, the aggregate shell first precisely fractures under stress stimulation, and the internal water-expanding layer then generates a strong driving force, prompting the self-healing agent in the carrier's slow-release core to be fully released into the crack. Through a chemical reaction, a dense and stable healing product is generated, thereby automatically and efficiently repairing the damage, restoring the structural integrity and mechanical properties, and significantly improving impermeability, corrosion resistance, and fatigue life.
[0022] 2. The intelligent repair system in this application achieves multi-stage, multi-mechanism synergistic response and controlled release. The ethyl cellulose shell provides robust physical protection and sensitive mechanical triggering; the calcium sulfoaluminate-based expansion layer ensures sufficient dynamism and efficiency in the release of the repair agent; and the polylactic acid carrier, through controlled degradation in an alkaline environment, achieves the matching of the slow release of the repair agent with the damage process. This synergistic mechanism overcomes the limitations of single response and one-time release, ensuring high reliability of the repair response, sufficiency of release, and persistence of action, enabling concrete to possess intelligent, precise, and continuous damage repair capabilities. Detailed Implementation
[0023] The following detailed description of this application is provided in conjunction with the embodiments. It should be noted that: unless otherwise specified, the conditions in the following embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following embodiments are all from commercially available sources.
[0024] The cementitious material is silicate cement, purchased from Qianfu Mineral Products Processing Plant in Lingshou County, with a strength grade of 32.5; the coarse aggregate is crushed stone with a particle size of 5mm to 10mm and 10mm to 20mm mixed in a mass ratio of 3:17, with a crushing value ≤12%.
[0025] Preparation examples of raw materials and / or intermediates Preparation Example 1 A smart dual-response aggregate is prepared by the following steps: (1) Preparation of core: Mix 10 kg of magnesium calcium silicate (self-healing agent) and 10 kg of polylactic acid (carrier material) evenly to obtain a mixture, add 1 kg of polyvinyl alcohol aqueous solution (binder solution) with a mass concentration of 5% to granulate, form core particles with a particle size of 1 mm, and dry; (2) Coating the intermediate layer: Disperse 7 kg of calcium sulfoaluminate in 3 kg of 3-5% hydroxypropyl methylcellulose aqueous solution to form a uniform expandable component slurry. Use fluidized bed spraying method to coat the expandable component slurry onto the surface of the core particles to form an intermediate layer with a thickness of 100 μm. (3) Coating the outer shell: 10 kg of ethyl cellulose is dissolved in 90 kg of acetone solvent to obtain a polymer coating solution. The polymer coating solution is coated on the outer surface of the intermediate layer by fluidized bed spraying to form an outer shell with a thickness of 65 μm, thereby obtaining intelligent dual-response aggregate.
[0026] Preparation Example 2 A smart dual-response aggregate is prepared by the following steps: (1) Preparation of core: 10 kg of sodium silicate (self-healing agent) and 6 kg of polylactic acid (carrier material) are mixed evenly to obtain a mixture. 0.64 kg of 5% polyvinyl alcohol aqueous solution (binder solution) is added to granulate and form core particles with a particle size of 0.5 mm. The mixture is then dried. (2) Coating the intermediate layer: 6 kg of calcium sulfoaluminate is dispersed in 2 kg of 3-5% hydroxypropyl methylcellulose aqueous solution to form a uniform expandable component slurry. The expandable component slurry is coated on the surface of the core particles by fluidized bed spraying to form an intermediate layer with a thickness of 150 μm. (3) Coating the outer shell: 15 kg of ethyl cellulose is dissolved in 95 kg of acetone solvent to obtain a polymer coating solution. The polymer coating solution is coated on the outer surface of the intermediate layer by fluidized bed spraying to form an outer shell with a thickness of 30 μm, thereby obtaining intelligent dual-response aggregate.
[0027] Preparation Example 3 A smart dual-response aggregate is prepared by the following steps: (1) Preparation of core: 10 kg of magnesium calcium silicate (self-healing agent) and 14 kg of polylactic acid (carrier material) are mixed evenly to obtain a mixture. 1.44 kg of 5% polyvinyl alcohol aqueous solution (binder solution) is added to granulate and form core particles with a particle size of 1.5 mm. The mixture is then dried. (2) Coating the intermediate layer: 8 kg of calcium sulfoaluminate is dispersed in 4 kg of 3-5% hydroxypropyl methylcellulose aqueous solution to form a uniform swelling component slurry. The swelling component slurry is coated on the surface of the core particles by fluidized bed spraying to form an intermediate layer with a thickness of 50 μm. (3) Coating the outer shell: Dissolve 5 kg of ethyl cellulose in 85 kg of acetone solvent to obtain a polymer coating solution. Use fluidized bed spraying to coat the outer surface of the intermediate layer with the polymer coating solution to form an outer shell with a thickness of 100 μm, thereby obtaining smart dual-response aggregate.
[0028] Example
[0029] Example 1
[0030] A self-compacting concrete, prepared by the following steps: Mix 45 kg of cementitious material, 70 kg of fine aggregate and 0.3 kg of polycarboxylate superplasticizer evenly, add 11 kg of water and stir to form a uniform slurry, add 75 kg of coarse aggregate and the remaining 4 kg of water, stir evenly, and finally add 1.5 kg of the intelligent dual-response aggregate prepared in Preparation Example 1, stir for 30-60 seconds and then discharge.
[0031] Example 2
[0032] A self-compacting concrete, prepared by the following steps: Mix 40 kg of cementitious material, 75 kg of fine aggregate and 0.2 kg of polycarboxylate superplasticizer evenly, add 11 kg of water and stir to form a uniform slurry, add 80 kg of coarse aggregate and the remaining 3 kg of water, stir evenly, and finally add 2 kg of the intelligent dual-response aggregate prepared in Preparation Example 1, stir for 30-60 seconds and then discharge.
[0033] Example 3
[0034] A self-compacting concrete, prepared by the following steps: Mix 50 kg of cementitious material, 85 kg of fine aggregate and 0.4 kg of polycarboxylate superplasticizer evenly, add 11 kg of water and stir to form a uniform slurry, add 70 kg of coarse aggregate and the remaining 5 kg of water, stir evenly, and finally add 1 kg of the intelligent dual-response aggregate prepared in Preparation Example 1, stir for 30-60 seconds and then discharge.
[0035] Example 4
[0036] A self-compacting concrete, which differs from Example 1 in that the smart dual-response aggregate added in this example is the one prepared in Preparation Example 2.
[0037] Example 5
[0038] A self-compacting concrete, which differs from Example 1 in that the smart dual-response aggregate added in this example is the one prepared in Preparation Example 3.
[0039] Example 6
[0040] A self-compacting concrete, differing from Example 1 in that 2 kg of calcium oxide is added in this example, comprising the following steps: Mix 45 kg of cementitious material, 70 kg of fine aggregate, 2 kg of calcium oxide and 0.3 kg of polycarboxylate superplasticizer evenly, add 11 kg of water and stir to form a uniform slurry, add 75 kg of coarse aggregate and the remaining 4 kg of water, stir evenly, and finally add 1.5 kg of the intelligent dual-response aggregate prepared in Preparation Example 1, stir for 30-60 seconds and then discharge.
[0041] Example 7
[0042] A self-compacting concrete, which differs from Example 6 in that 3.5 kg of calcium oxide is added in this example.
[0043] Example 8
[0044] A self-compacting concrete, which differs from Example 6 in that 5 kg of calcium oxide is added in this example.
[0045] Comparative Example Comparative Example 1 A self-compacting concrete, which differs from Example 1 in that no smart dual-response aggregate was added in this comparative example.
[0046] Performance testing Detection methods / test methods
[0047] Compressive strength: 100mm×100mm×100mm cubic specimens were used, and the loading rate was 1MPa / s. The compressive and flexural strength of the specimens at 28d were tested according to GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". Durability: The test was conducted according to the relevant test methods in GB / T 50082-2024 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The freezing temperature and thawing temperature of the sample were -20℃~-15℃ and 6℃-8℃, respectively. The time for one freeze-thaw cycle was 4 hours. After 200 freeze-thaw cycles, the mass of the sample block before and after the test was tested and the mass loss rate was calculated. Self-healing performance: Tested after the specimen was pre-cracked to a crack width of 0.15 mm and cured under standard conditions for 28 days. Table 1. Test Results of Basic Mechanical Properties
[0048] Table 2 Self-healing performance test results
[0049] Combining Examples 1-3 and Comparative Example 1 with Tables 1-2, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 1, indicating that the introduction of intelligent dual-response aggregate can realize the self-healing of self-compacting concrete. Its multi-level core-shell structure can effectively respond to cracks and release healing agents, thereby significantly improving its crack self-healing efficiency and durability recovery ability without significantly affecting the workability and mechanical properties of concrete.
[0050] As can be seen from Examples 1-5 and Tables 1-2, the addition of the intelligent dual-response aggregate prepared by the method of this application can stably and reliably impart excellent self-healing properties to self-compacting concrete within a range of parameters such as the type of self-healing agent, carrier, and coating thickness. This verifies the universality and effectiveness of the functional aggregate obtained by the preparation method, and ensures the sensitive response and efficient healing of the repair system to microcracks.
[0051] Combining Examples 1 and 6-8 with Table 1-2, it can be seen that the appropriate amount of calcium oxide can produce a significant synergistic enhancement effect with the intelligent dual-response aggregate. By increasing the alkalinity of the matrix and promoting early hydration, it not only optimizes the mechanical properties of concrete, but also further accelerates and strengthens the self-healing process, so that the crack repair rate, impermeability recovery rate and strength recovery rate are systematically improved, achieving the dual effect of matrix performance enhancement and intelligent repair efficiency amplification.
[0052] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A self-compacting concrete, characterized in that, Including the following parts by weight of raw materials: The mixture comprises 400-500 parts of cementitious material, 700-800 parts of coarse aggregate, 750-850 parts of fine aggregate, 140-160 parts of water, 10-20 parts of intelligent dual-response aggregate, and 2-4 parts of polycarboxylate superplasticizer. The intelligent dual-response aggregate is a functional particle with a core-shell structure, which is encapsulated with a self-healing agent. The preparation of the intelligent dual-response aggregate includes the following steps: (1) Preparation of core: The self-healing agent and the carrier material are mixed at a weight ratio of 1:(0.6-1.4) to obtain a mixture. 4-6% by mass of the binder solution is added to granulate the mixture to form core particles with a particle size of 0.5-1.5 mm. The mixture is then dried. (2) Coating intermediate layer: The expansive component slurry is coated onto the surface of the core particles using a fluidized bed spraying method, and the intermediate layer is formed after drying; (3) Coating the outer shell: The polymer coating solution is coated on the outer surface of the intermediate layer by fluidized bed spraying. After drying, an outer shell with a thickness of 30-100μm is formed to obtain the intelligent dual-response aggregate with a particle size of 1-5mm. The self-healing agent is either magnesium calcium silicate or sodium silicate. The expandable slurry contains 60-80 parts of calcium sulfoaluminate and 20-40 parts of a 3-5% aqueous solution of hydroxypropyl methylcellulose. The polymer coating solution is obtained by dissolving 5-15 parts of ethyl cellulose in 85-95 parts of an organic solvent; The carrier material is polylactic acid.
Citation Information
Patent Citations
Self-repair material, concrete with self-repair material and preparation thereof
CN105645826A
Permeable crystallization type self-repairing concrete structure and manufacturing method thereof
CN108751869A
Self-repairing special concrete and preparation method thereof
CN120423828A
High-strength self-compacting concrete for complex steel structure and preparation method of high-strength self-compacting concrete
CN122233725A